Moving to Sustainable Buildings : Paths to Adopt Green Innovations in Developed Countries - Berardi, Umberto (Versita discipline : arts, music, literature, 2013)
"Umberto Berardi explores the transition of the construction sector to sustainable building through the adoption of green innovations. Applying methods ranging from theoretical discussions to interviews and field studies, Berardi describes how organisational models among stakeholders are changing as the sector moves towards a green economy"--Publisher's description.